Magnetic resonance imaging in neuropsychiatric systemic lupus erythematosus: current state of the art and novel approaches. (April 2017) - Postal, M; Lapa, A Tamires; Reis, F; Rittner, L; Appenzeller, S
Systemic lupus erythematosus is a chronic, inflammatory, immune-mediated disease affecting 0.1% of the general population. Neuropsychiatric manifestations in systemic lupus erythematosus have been more frequently recognized and reported in recent years, occurring in up to 75% of patients during the disease course. Magnetic resonance imaging is known to be a useful tool for the detection of structural brain abnormalities in neuropsychiatric systemic lupus erythematosus patients because of the excellent soft-tissue contrast observed with MRI and the ability to acquire multiplanar images. In addition to conventional magnetic resonance imaging techniques to evaluate the presence of atrophy and white matter lesions, several different magnetic resonance imaging techniques have been used to identify microstructural or functional abnormalities. This review will highlight different magnetic resonance imaging techniques, including the advanced magnetic resonance imaging methods used to determine central nervous system involvement in systemic lupus erythematosus.